Back Cover: Electropolymerisation of Catalytically Active PEDOT from an Ionic Liquid on a Flexible Carbon Cloth Using a Sandwich Cell Configuration (ChemPlusChem 1/2015). Issue 1 (January 2015) - Abdelhamid, Muhammad E.; Snook, Graeme A.; O'Mullane, Anthony P.
<x xml:space="preserve">Abstract</x> The back cover picture shows a carbon cloth electrode being coated with the conducting polymer poly(3, 4‐ethylenedioxythiopene) PEDOT via an electrochemical process using a sandwich cell configuration. The cloth maintains its flexibility while ensuring a homogeneous coverage with PEDOT. The electrode is then used as an oxygen reduction catalyst which operates under both alkaline and acidic conditions while also being tolerant to the presence of methanol in the electrolyte. Details are given in the Full Paper by Anthony P. O'Mullane et al. on page 74).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>